The Impact of the Internet of Things (IoT) on Healthcare Delivery: A Systematic Literature Review - Bismark Atta Frimpong; Cláudia Barbosa; Raed A Abd-Alhameed (Journal of Techniques)
The Internet of Things (IoT) also has a huge impact on dramatically lowering healthcare expenses and increasing treatment outcomes. The only ways that patients could communicate with doctors before the Internet of Things were in person, over the phone, or via text. There was no feasible way for healthcare providers to assess patients’ health and offer advice continuously. IoT-enabled technological equipment has made remote monitoring possible in the healthcare industry, opening opportunities to keep patients safe and healthy and empowering medical professionals to provide the best treatment possible. This review provides a comprehensive study of the literature on IoT’s impact (negative or positive) on healthcare delivery and why it is difficult to implement despite its enormous benefits. Search engines (journal publishing databases) like Google Scholar, PubMed, and ScienceDirect were used to find studies on the impact of IoT-based healthcare delivery. Data were extracted from papers found, and the quality of studies that qualified for inclusion and exclusion was assessed and reported. It includes the proposed technologies’ validation as well as their clinical effectiveness. The review found that the lack of government commitment to financing IoT projects is a challenge to its implementation in healthcare delivery since it involves huge capital at the beginning and its maintenance. In addition, some medical professionals are still acquainted with the old-fashioned (manual) ways of delivering their services, hence avoiding the technological approach. Despite the challenges, one noted the positive effect of IoT in healthcare delivery is that doctor-patient interactions have gotten simpler and more effective; it has also raised patient participation and satisfaction. Furthermore, remote patient monitoring shortens hospital stays and avoids readmissions by monitoring patients’ health.